Penyatuan Istilah dalam Studi Ilmu Tafsir (Eksplorasi Keragaman Istilah Metodologi dalam Tafsir) - Zulaiha, Eni (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Standardization of Terminology in Tafsir Studies (Exploring the Diversity of Methodological Terminology in Tafsir) This article aims to find to offer a uniformity of terms in the science of exegesis. This study uses a qualitative method by implementing library research with content analysis. The results of this study indicate that the causes of differences in the use of terms in the science of interpretation are due to differences in paradigms and the use of terms that do not come from the interpreter and the original source. Thus, a more mature study is needed on the use of technical terms and the constructs of the science of interpretation itself. Meanwhile, the offer of terms and construction of the science of interpretation focuses on the study of the sources of interpretation, the method of interpretation and the style of interpretation, because these three are the essence and basis of the science of interpretation. The conclusion of the research proves that in the study of exegesis there are differences in the use of terms that come from restrictions on different definitions in the discussion of sources, methods and styles of interpretation. It takes a uniform use of terms to facilitate learning interpretation and several other sciences related to it. This study recommends that further research be carried out on other technical terms in the study of interpretation.